El Niño/Southern Oscillation response to low-latitude volcanic eruptions depends on ocean pre-conditions and eruption timing - Evgeniya Predybaylo (Nature Portfolio, 2020)
The Pacific ocean response to low-latitude volcanic eruptions depends on ENSO phase, eruption magnitude and stochastic effects, suggests a grand ensemble of climate model simulations.